Tahap Penerimaan Pelajar Kejuruteraan Elektrik dan Elektronik terhadap Penggunaan Augmented Reality (AR) E-Modul Subjek Asas Mikropemproses - Bakarudddin, Adibah; ABDULLAH, NURHANIM (Research and Innovation in Technical and Vocational Education and Training, 2025)
The subject Fundamentals of Microprocessor is a core course for Bachelor of Electrical and Electronic Engineering students at Universiti Tun Hussein Onn Malaysia (UTHM). However, there are issues related to the lack of Augmented Reality (AR) technology usage in this subject, the institution's readiness in providing technological infrastructure, as well as the use of conventional teaching approaches that are less interactive. AR technology now holds great potential to revolutionize education by providing a more interactive and engaging learning experience for students. Therefore, this study aims to develop an AR-assisted Fundamentals of Microprocessor e-Module, evaluate its functionality, and identify students' acceptance levels in terms of design, content, and usability. The e-Module was developed using the ADDIE model and is based on constructivist and cognitive learning theories. It was designed using the Heyzine platform with AR integration through the Makar application. The content includes notes, videos, and quizzes to assess students’ understanding. A quantitative approach was used in this study involving 25 Electrical and Electronic Engineering students as respondents. Additionally, the functionality of the e-Module was evaluated by two experts. The expert evaluation indicated a high level of functionality, with positive feedback regarding its design, content, and usability. However, several suggestions were provided to improve the module's quality, such as adding introductions to videos and enhancing navigation elements. A questionnaire was also used to assess students' acceptance of the e-Module after using it independently. Descriptive analysis results showed that students’ acceptance levels in terms of design, content, and usability were high. Students gave positive feedback on the interactive elements, flexibility of the module, and its ability to support better self-directed learning. Overall, this study successfully developed an AR-assisted Fundamentals of Microprocessor e-Module that meets the research objectives. The findings of this study are expected to serve as a guide for educators and institutions in integrating AR technology as an innovative and effective teaching aid.